“Snake”, “Life” or “Mother of All Living”? The Meaning of the Name חַוָּה (Eve) And Its Role in Gen 3 - Napora, Krzysztof (Verbum Vitae, 2022)
In Gen 3:20, the redactor of the Book of Genesis reports for the second time the scene of naming the woman created by God from Adam’s rib (cf. Gen 2:21-23). The name אשׁה (woman) used by Adam in Gen 2:23 obviously relates—at least phonetically—to the noun אישׁ (man). In this way, the editor expresses the idea of a certain relationship between man and woman. The existence of a similar, simple connection between the name חַוָּה (Eve) and the title אם כל־חי (the mother of all living) is far less obvious and this conundrum has been noticed by translators and exegetes for at least 2000 years. An echo of these difficulties seems to be perceptible in the text of the Septuagint, in the writings of Philo and Josephus, in the Targums, as well as in the writings of some ancient Christian writers. This article represents one further attempt to present the panorama of modern hypotheses concerning Eve’s name and the role this naming play in Gen 3.